Incidence rate and related factors of depression in older adult patients with somatization symptoms - Tang, Liming; Zhong, Jinrong; Li, Fengjin; Zeng, Mei’e; Deng, Weiwei; Ye, Shuifen; Huang, Chunmei; Lai, Dongqin; Qiu, Hanzhong; Chen, Bin; Deng, Xiaoyuan; Zou, Bilan (Frontiers in Public Health, 2025)
BackgroundThis study aimed to determine the incidence and predictors of depressive symptoms among older adults presenting with somatization symptoms. A prospective cohort design was used to follow participants over time and evaluate the emergence of depressive symptoms.MethodsBetween July 2020 and November 2022, 162 community-dwelling adults aged ≥60 years were enrolled from three community health centers in Fujian Province. Participants screened positive for moderate-to-severe somatization (Somatic Self-Rating Scale, SSS ≥ 38) but negative for depression (Patient Health Questionnaire-2, PHQ-2 < 3) at baseline. Depressive symptoms were reassessed using PHQ-2 at 3, 6, and 12 months. Those scoring ≥3 underwent confirmatory screening with the PHQ-9 (cutoff ≥10). Predictors of incident depressive symptoms were identified using purposeful multivariable logistic regression, with Firth correction applied for small-cell bias. Confounding structure was guided by a directed acyclic graph (DAG), and internal consistency was assessed (SSS: Cronbach’s α = 0.89; PHQ-2: α = 0.78).ResultsDuring the 12-month follow-up, 20.37% of participants (n = 33) developed clinically significant depressive symptoms. Baseline somatization severity was moderately correlated with subsequent PHQ-2 scores (r = 0.565, p < 0.001). Multivariable analysis identified two independent predictors: resident medical insurance (aOR = 0.068, 95% CI: 0.009–0.512) and living with children (aOR = 0.305, 95% CI: 0.102–0.915), both associated with increased risk. The final model demonstrated good calibration (Hosmer–Lemeshow p = 0.676) and excellent discrimination (AUC = 0.862). Sensitivity analysis including individuals with mild somatization (SSS ≥ 30) confirmed the robustness of findings.ConclusionAmong older adults with somatization symptoms, depressive symptoms emerged in over 20% within 12 months. Individuals with resident health insurance or living with children may face increased psychosocial stressors contributing to depression risk. Early identification and targeted psychosocial interventions are warranted, especially in settings where somatic presentations may mask mental health needs.